2010
DOI: 10.1007/s10340-010-0297-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cotton cultivars on the oviposition preference of pink bollworm (Lepidoptera: Gelechiidae)

Abstract: The effect of four cotton cultivars on the oviposition behavior of the pink bollworm Pectinophora gossypiella (Saunders) was studied under laboratory and semi-field conditions. Young plants and bolls from four commercial upland cotton cultivars (Lachata, Macnair-220, Midas and Sandra) cultivated in the area of Thessaloniki were used. The four cultivars had palmate leaves, and nectaries on both leaves and bolls. Differences were observed in the trichome density and the length of leaf petiole among the cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Optimal oviposition theory predicts that adult preference should correlate with host plant suitability for the development of offspring (Jaenike 1978). However, the existing data range from positive correlations between adult preference and offspring performance (Ahman 1985;Singer et al 1988;Kouki 1993;Nylin et al 1996;Bertheau et al 2009;Afsaneh et al 2011), to poor or no correlations (Jallow and Zalucki 2003;Ladner and Altizer 2005;Rajapakse and Walter 2007;Chatzigeorgiou et al 2010;Shikano et al 2010). Many hypotheses (e.g., enemy free space) have been advanced to explain the variation in the relationship between adult preference and offspring performance (Thompson 1988;Craig et al 1989).…”
Section: Introductionmentioning
confidence: 93%
“…Optimal oviposition theory predicts that adult preference should correlate with host plant suitability for the development of offspring (Jaenike 1978). However, the existing data range from positive correlations between adult preference and offspring performance (Ahman 1985;Singer et al 1988;Kouki 1993;Nylin et al 1996;Bertheau et al 2009;Afsaneh et al 2011), to poor or no correlations (Jallow and Zalucki 2003;Ladner and Altizer 2005;Rajapakse and Walter 2007;Chatzigeorgiou et al 2010;Shikano et al 2010). Many hypotheses (e.g., enemy free space) have been advanced to explain the variation in the relationship between adult preference and offspring performance (Thompson 1988;Craig et al 1989).…”
Section: Introductionmentioning
confidence: 93%
“…When larvae are limited in their abilities to relocate, the female's choice of oviposition sites strongly influences their offspring's performance (Thompson & Pellmyr 1991;Zalucki et al 2002;Bertheau et al 2009;Clark et al 2011;Mazaheri et al 2011;Zhang et al 2012). However, many other studies have revealed that adult choice and offspring performance are frequently poorly correlated (Jallow & Zalucki 2003;Brodbeck et al 2007; Gripenberg et al 2007;Chatzigeorgiou et al 2010;Shikano et al 2010). Some adult females select host plants to obtain more nutrition for themselves, even when it decreases offspring performance (Scheirs & Bruyn 2002), or to minimize the influence of natural enemies or disease on their offspring, mortality factors frequently overlooked in laboratory assays (Barbosa & Krischik 1987;Valladares & Lawton 1991;Clark et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on P. gossypiella involving rearing of field‐collected insect samples use natural oviposition substrates, like cotton twigs (with terminal leaves and buds; Dhara Jothi et al., ) or cotton squares (Muralimohan et al., ) which need to be replenished with fresh substrate at regular intervals to ensure sufficient eggs. Previous studies on the oviposition behavior of pink bollworm have investigated the acceptability of various cotton cultivars (Wilson et al., ; Chatzigeorgiou et al., ), but there are only limited studies on the use of artificial substrate for egg laying. Hence, relying on natural substrates for oviposition is the most common method used by researchers for P. gossypiella , although the use of natural substrates for oviposition requires the maintenance of plants in the field or under greenhouse conditions, which is highly resource intense in terms of labor, cost, and time.…”
Section: Discussionmentioning
confidence: 99%